Navigation of Pedagogical Excellence: Mobile Learning’s Moderating Effect on Teachers’ Pedagogical Competency and Professional Competency in Evaluating Students Religious Characters - Fajar Shodiq Sadam; Makrufi Anisa Dwi; Najib Khotim Hanifudin; Goselfa Limason; Valencia Nadira Putri; Nurunisa Fadhila Aisyah (SHS Web of Conferences)
This study examines the impact of mobile learning on teachers’ pedagogical and professional competencies as well as their religious disposition. The research was carried out at SMA Muhammadiyah 6 and SMA Muhammadiyah 5 Yogyakarta with the aim of gaining a deeper comprehension of mobile learning in the context of education. This study employed a quantitative research design and recruited a total of 102 individuals through the use of random sampling. Information was gathered through the use of questionnaires consisting of 34 statements. The questionnaire responses exhibited high dependability, as shown by a reliability coefficient of 0.7. Hypotheses were tested using multiple linear regression. The study revealed that teachers’ educational and professional competencies enhance their religious nature. The initial moderating influence had a notable adverse effect on the religious nature, but the later influence was favourable. The results did not provide evidence to support the hypothesis that mobile learning had a moderating effect on these talents and religious character. The schools SMA Muhammadiyah 6 and 5 in Yogyakarta provide evidence that the implementation of mobile learning enhances teaching methods and fosters the promotion of Islamic principles. These findings indicate that instructors and students must comprehend the learning process in order to attain the best possible educational outcomes. Mobile learning can be included into the teaching and evaluation processes at educational institutions to anticipate educational progress.